Collateral scarcity premia in euro area repo markets - Massimo Ferrari; Claudia Guagliano; Julien Mazzacurati (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
Collateral plays a very important role in financial markets. Without easy access to high-quality collateral, dealers and market participants would find it more costly to trade, with a negative impact on market liquidity and the real economy through increased financing costs. The role of collateral has become increasingly significant since the global financial crisis, partly due to regulatory reforms. Using bond-level data from both repo and securities lending markets, this paper introduces a new measure of collateral reuse and studies the drivers of the cost of obtaining high-quality collateral, i.e. the collateral scarcity premium, proxied by specialness of government bond repos. We find that the cost of obtaining high-quality collateral increases with demand pressures in the cash market (short-selling activities), even in calm financial market conditions. In bear market conditions - when good collateral is needed the most - this could lead to tensions in some asset market segments. Collateral reuse may alleviate some of these tensions by reducing the collateral scarcity premia. Yet, it requires transparency and monitoring due to the financial stability risks associated. Finally, we find that the launch of the ECB quantitative easing programme has a statistically significant, albeit limited, impact on sovereign collateral scarcity premia, but this impact is offset by the beginning of the ECB Securities Lending Programme.
Keywords: E52; G12; G23; 330; Repos; securities lending; collateral; specialness; short selling; collateral reuse; negative interest rates; quantitative easing